Etiopatogenia da hanseníase - Minelli, Lorivaldo (2004)
The author make a brief sudy about etimologycal and pathogenic aspects of the Hanseniasis. He compares the different evolutions of the Virchowian, Tuberculoid, Dimorphous and Indetermined Patients.